Utilization of Digital Media in Second Language Acquisition: A Psycholinguistic Perspective on Learning - Asia M (Newinera Publisher, 2026)
This study investigates the utilization of digital media in second language acquisition from a psycholinguistic perspective among elementary school students in Makassar City. As digital technologies increasingly shape contemporary learning environments, understanding their cognitive, linguistic, and motivational impacts is essential for strengthening instructional practices. Employing a qualitative research design, this study draws on in-depth interviews with teachers, classroom observations, and document analysis to explore how digital media influences students’ comprehension, memory encoding, and engagement during English language learning. The findings reveal that digital media significantly enhances learners’ cognitive engagement by capturing attention through multimodal features such as animation, sound, and interactivity. These elements reduce cognitive load and support sustained focus, allowing students to process linguistic input more effectively. The study also demonstrates that digital media facilitates deeper comprehension by providing immediate contextual cues visual, auditory, and symbolic that help young learners grasp vocabulary and sentence structures without relying on translation. Furthermore, repetitive and visually supported digital content strengthens memory encoding, enabling students to retain and recall language items more reliably. Various types of digital media including videos, interactive learning applications, digital games, and presentation tools were found to serve complementary pedagogical functions that teachers employed strategically to support linguistic development. Overall, the study concludes that digital media, when thoughtfully integrated, acts as a powerful tool that enriches cognitive processing, reinforces memory, and fosters a more engaging and inclusive learning environment. These insights highlight the need for continued professional development and infrastructural support to maximize the pedagogical potential of digital media in elementary second language education.